Implementasi Keadilan Restoratif dalam Penegakan Hukum Kepabeanan dan Cukai - Bagman Roy Manalu (Jurnal Indonesia Sosial Sains, 2022)
The enforcement of criminal law in the field of customs and excise is still focused on imposing criminal penalties or sanctions against perpetrators. Settlement of customs and excise cases should focus on recovering losses in state revenues because Import Duties, Export Taxes (Export Duties), and Excise are the main sources of state revenue. This study aims to examine the concept of criminalizing customs and excise criminals in the perspective of restorative justice and the implementation of restorative justice in customs and excise law enforcement. This study uses a normative juridical approach through the study of legal theories and legislation related to research problems. The results of this study are that the concept of restorative justice has been adopted in Customs and Excise Law but legislation should be issued immediately relating to procedures for stopping investigations in the interest of state finances so that a restorative justice approach can be applied in the settlement of customs and excise cases.